Use of green building information modeling in the assessment of net zero energy building design - Chen, Shang Yuan (Journal of Environmental Engineering and Landscape Management, 2019)
In the face of extreme climate, Net Zero Energy Buildings (NZEBs) represent a very high standard of building energy conservation. The design of NZEBs requires continuous design improvement and analysis in a decision-making process that seeks to meet energy conservation goals. This paper recommends the use of green Building Information Modelling (BIM) to support the design of zero-energy buildings. The design of NZEBs requires two sets of tasks: First, it requires determination of whether the building will offer high-energy efficiency, and, second, it lacks the installation of sufficient renewable energy equipment to meet the building’s load needs. After drawing on the spirit of the United States’ Leadership in Energy and Environmental Design and considering the current situation in Taiwan, this paper recommends the use of electricity Energy Usage Intensity as a measurement unit providing a holistic indicator of energy usage and takes optimized energy performance as a performance target for various solutions. This study demonstrated procedural steps in the application of green BIM and analyzed restrictions on the implementation of green BIM to the analysis of NZEB design.